Answer: 1
Step-by-step explanation:
3x + 8x-8= 3
11x-8=3
Then you move the 8 to the other side and change it to a positive.
11x= 11
11x/11 = 11/11
Answer is 1
Answer:
I will assume that the term "x+2/2" is meant to be "(x + 2)/2)." Otherwise the equation would read (x/3) = x + 1
Step-by-step explanation:
(x/3) = (x + 2)/2
x = 3*(x+2)/2 [Multiply both sides by 3]
x = (3x + 6)/2
x = (3/2)x + 6/2
x - (3/2)x = 3
-0.5x = 3
x = -6
====================
Check:
Does (x/3) = (x + 2)/2 for x = -6?
(-6/3) = (-6 + 2)/2
-2 = -4/2
-2 = -2 YES
Answer:
its 2 ounces. if you look it up it would tell you